Preparation method of diamond silver-nano silver solder paste, solder paste and welding method
By plating silver cladding on the surface of nanodiamond particles and doping them in nanosilver paste, diamond silver-nano silver solder paste is prepared by magnetron sputtering technology, the problem of poor thermal conductivity of existing nanosilver solder paste is solved, and a solder paste with high thermal conductivity and electrical conductivity is achieved.
Patent Information
- Application Number
- CN202211516129.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-11-29
AI Technical Summary
The existing nano silver solder paste has problems such as gaps and fractures during the preparation process, resulting in unsatisfactory thermal conductivity and difficulty in bonding with the metal interface between the non-metal reinforced phase and the metal, affecting the thermal conductivity.
Magnetic sputtering technology is used to plate silver cladding on the surface of nanoscale diamond particles to form nanodiamond silver particles, and dopant them in nanosilver paste. Diamond silver-nano silver solder paste is prepared by mixing it at room temperature through magnetron sputtering technology.
It significantly improves the thermal conductivity and electrical conductivity of solder paste, and the thermal conductivity can reach more than 400W/(m·K), while maintaining high bonding strength, solving the problem of difficulty in bonding between non-metal nanomaterials and metal interfaces.
Smart Images

Figure BDA0003970535240000061 
Figure HDA0003970535250000011 
Figure HDA0003970535250000012
Abstract
Description
Technical Field
[0001] The present application belongs to the field of magnetron sputtering technology, and specifically relates to a preparation method of diamond silver nano-silver solder paste, solder paste and welding method. Background Art
[0002] Due to the rapid development of the electronics industry, power electronic devices are increasingly used in various fields. Among them, the various properties of interconnect materials working in high-power environments are extremely important. As a new type of interconnect material, nanosilver solder paste has excellent conductivity, high melting point and low sintering temperature. However, due to the different application devices, it is very easy to cause fatal problems such as gaps and fractures in the preparation process of nanosilver solder paste, which reduces the heat dissipation capacity.
[0003] There are a lot of studies on improving the thermal conductivity of nano silver solder paste, and the main approach is to add a reinforcing phase. The existing technology mainly adds reinforcing phases with high thermal conductivity such as graphene, diamond, and aluminum nitride. However, due to the uneven dispersion and loose bonding between the reinforcing phase and the nano silver material during the preparation process, the adhesion strength and thermal conductivity need to be improved. At the same time, the above-mentioned reinforcing phases are basically non-metallic materials, which will cause the conductivity of the nano silver solder to decrease.
[0004] In the prior art, nano-silver paste is doped with nano-diamond or nano-aluminum nitride particles. During the sintering process, it is difficult to form a sintering neck between the diamond particles or aluminum nitride particles and the nano-silver particles, thereby hindering the contact between the nano-silver particles. For example, an independent nano-silver particle may have only one or two parts of its surface that can contact other nano-silver particles. Therefore, the sintered structure formed is a two-dimensional long chain structure, and finally a pine cone-shaped sintered structure composed of a two-dimensional chain structure is formed, resulting in the final thermal conductivity of the nano-silver paste after sintering is not ideal. Summary of the invention
[0005] In order to solve the problem of poor thermal conductivity of the prepared composite material caused by the difficulty in combining non-metallic nanomaterials with metal interfaces, the present application provides a method for preparing diamond silver-nanosilver solder paste, which includes the following steps in order:
[0006] S1: Cleaning of nano-scale diamond particles;
[0007] S2: using a magnetron sputtering process to first deposit a transition layer on the surface of nano-scale diamond particles, and then depositing silver on the surface of the transition layer to obtain nano-diamond silver particles;
[0008] S3: adding nanosilver particles into an organic solvent and mixing them evenly to obtain a nanosilver slurry;
[0009] S4: mixing the nano-diamond silver particles obtained in step S2 with the nano-silver slurry obtained in step S3 at room temperature to obtain diamond silver-nano-silver solder paste.
[0010] The nano-diamond silver particles formed in step S2 are diamond core-shell structures with nano-scale diamond particles as cores and coated with silver.
[0011] Furthermore, in step S1, the cleaning process includes ultrasonic cleaning and plasma cleaning in sequence;
[0012] The ultrasonic cleaning comprises: firstly soaking the nano-scale diamond particles in acetone, then soaking them in anhydrous ethanol, ultrasonically cleaning them in pure water, and then drying them in a vacuum environment;
[0013] The plasma cleaning conditions are: the plasma cleaning process is performed for 20 minutes to 40 minutes at a gas pressure of 0.5Pa to 5Pa, an argon gas flow rate of 400sccm to 500sccm, a temperature of 100°C, and a bias voltage of -800V to -500V.
[0014] Furthermore, the step S2 also includes the following steps:
[0015] S2.1: Select target material: Select a silver target with a purity higher than 99.99% as the sputtering target;
[0016] S2.2: Sputtering transition layer: The material of the transition layer is selected from one of Ni, Cr, and Ti; the applied bias voltage is -80V to -60V, the power is 0.5kW to 2kW, the gas pressure is 0.2Pa to 1Pa, the sputtering time is 5min to 10min, and the pre-sputtering thickness is 5nm to 10nm; during the magnetron sputtering process, an ultrasonic vibration system is used to vibrate the diamond particles so that the diamond particles tumble during the deposition process to ensure that the surface of each diamond particle is evenly coated with the transition layer;
[0017] S2.3: Use DC magnetron sputtering to plate a silver coating on the surface of the diamond particles on which the transition layer is deposited: fill with argon gas, adjust the pressure in the sputtering chamber to 0.2Pa~0.5Pa, the sputtering power to 0.5kW~2kW, the bias voltage to -80V~-60V, the sputtering time to 10min~20min, and the thickness of the pre-sputtered Ag layer to 15nm~25nm. During the magnetron sputtering process, an ultrasonic vibration system is used to vibrate the diamond particles so that the diamond particles tumble during the deposition process to ensure the uniformity of deposition on each surface of each particle. Finally, nano-diamond silver particles are obtained.
[0018] S2.4: Heat treatment: Heat treatment is carried out in an atmosphere of argon at normal pressure, the heat treatment temperature is 600°C to 800°C, and the heat treatment time is 1h to 1.5h.
[0019] Furthermore, in step S2, the average particle size of the nano-scale diamond particles is 20 nm to 40 nm, and the average particle size of the prepared nano-diamond silver particles is 80 nm to 120 nm.
[0020] Furthermore, in step S3: preparing the nano silver slurry further comprises:
[0021] Add nanosilver particles into an organic solvent containing a surfactant.
[0022] Then a spiral oscillator is used for mechanical oscillation, and finally ultrasonic stirring is used to obtain nano silver slurry; the average particle size of the nano silver particles is 40nm to 80nm.
[0023] Furthermore, in step S3, the organic solvent is preferably anhydrous ethanol; the surfactant is preferably polyvinyl pyrrolidone (PVP); and the mass ratio of the surfactant to the nanosilver particles is 1:13 to 1:17.
[0024] Furthermore, in step S3, the time for mechanical oscillation using the spiral oscillator is 10 minutes to 20 minutes, and the time for ultrasonic stirring using the ultrasonic cleaner is 40 minutes to 60 minutes.
[0025] Furthermore, in step S4, the mass ratio of nano-diamond silver particles to nano-silver slurry is 1:15 to 1:30.
[0026] Furthermore, in step S4, the stirring time of the mixer is 1 hour to 1.5 hours, wherein the mechanical oscillation is firstly performed by a spiral oscillator for 20 minutes to 30 minutes, and then the ultrasonic cleaning device is used for ultrasonic oscillation for 40 minutes to 60 minutes.
[0027] Due to the excellent thermal conductivity of diamond and the excellent electrical conductivity of silver, the diamond silver-nanosilver solder prepared by the present application has high electrical and thermal conductivity, and its thermal conductivity can be increased to more than 400 W / (m·K).
[0028] Beneficial Effects
[0029] The present application proposes a method for preparing a diamond silver-nanosilver solder paste and a diamond silver-nanosilver solder paste, which utilizes magnetron sputtering technology to plate a silver coating on the surface of diamond and then dopes it in nanosilver paste. Compared with the traditional nanosilver paste without doping with an enhanced phase, the present method can significantly improve its thermal conductivity without affecting the conductive properties by doping diamond silver core-shell structure particles in the nanosilver paste. Compared with the existing method of doping with other non-metallic enhanced phases, the present application effectively keeps the conductive properties of nanosilver unaffected by plating a silver coating on the surface of diamond particles by magnetron sputtering, and can effectively improve the chemical inertness of the surface of diamond particles, enhance the interface bonding ability between it and nanosilver particles, improve the heat transfer characteristics of the composite material, and solve the problem of the difficulty of bonding between non-metallic nanomaterials and metal interfaces.
[0030] The diamond silver-nano silver solder prepared in the present application has strong electrical conductivity, high thermal conductivity, high bonding strength and high practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : Schematic diagram of the preparation process of diamond silver-nanosilver solder paste;
[0032] Figure 2 : Schematic diagram of the surface of nano-silver particles melting and then aggregating and fusing around nano-diamond silver particles;
[0033] Figure 3 : Schematic diagram of sintering neck formed by nano-silver particles and nano-diamond silver particles;
[0034] Figure 4 : Overall schematic diagram of sintering of silver nanoparticles to form densification. DETAILED DESCRIPTION
[0035] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to the accompanying drawings.
[0036] Embodiment 1
[0037] The present application provides a method for preparing diamond silver-nano silver solder paste, such as Figure 1 As shown, the specific implementation steps are as follows:
[0038] S1: Ultrasonic cleaning and plasma cleaning of nano-scale diamond particles;
[0039] S2: Using magnetron sputtering to deposit a transition layer on the surface of nano-scale diamond particles, and then coating them with silver to obtain nano-diamond silver particles;
[0040] S3: preparing nano silver slurry: adding 0.5 g of nano silver particles into 25 ml of organic solvent, adding 0.03 g of surfactant, and then mechanically oscillating with a spiral oscillator, and finally ultrasonically stirring with an ultrasonic cleaner to obtain nano silver slurry;
[0041] S4: Preparation of diamond silver-nano silver solder paste: Nano-diamond silver particles are mixed with nano-silver slurry at room temperature, and stirred with a mixer until the particles are evenly dispersed. After washing and centrifugal separation, diamond silver-nano silver solder paste is obtained.
[0042] Furthermore, in step S1, the ultrasonic cleaning step is: under the condition of a vibration frequency of 40kHz, first immerse in acetone for 10 minutes, then immerse in anhydrous ethanol for 5 minutes, rinse the cleaned object with water, then ultrasonically clean it in pure water for 8 minutes, and finally spread it flat in a vacuum environment at 120°C and dry it for 60 minutes.
[0043] Furthermore, in step S1, the plasma cleaning conditions are: plasma cleaning for 40 minutes at a gas pressure of 1 Pa, an argon gas flow rate of 400 sccm, a temperature of 100° C., and a bias voltage of −500 V;
[0044] Furthermore, the step S2 also includes the following steps:
[0045] S2.1: Select target material: Select silver target with purity higher than 99.99% as sputtering target material;
[0046] S2.2: Sputtering transition layer: Cr is selected as the transition layer metal. The applied bias voltage is -60V, the power is 0.5kW, the gas pressure is 0.2Pa, the sputtering time is 5min, and the thickness of the sputtered Cr layer is 10nm; during the magnetron sputtering process, an ultrasonic vibration system is used to vibrate the diamond particles so that the diamond particles tumble during the deposition process to ensure the uniformity of deposition on each surface of each particle.
[0047] S2.3: Use DC magnetron sputtering to plate a silver coating on the surface of the diamond particles on which the transition layer is deposited: fill with argon gas, adjust the pressure in the sputtering chamber to 0.2Pa, the sputtering power to 0.5kW, the bias voltage to -60V, the sputtering time to 10min, and the thickness of the sputtered Ag layer to 20nm. During the magnetron sputtering process, an ultrasonic vibration system is used to vibrate the diamond particles so that the diamond particles tumble during the deposition process to ensure the uniformity of deposition on each surface of each particle. Finally, nano-diamond silver particles are obtained.
[0048] S2.4: Heat treatment: Heat treatment is carried out under normal pressure argon atmosphere, the heat treatment temperature is 220°C, and the heat treatment time is 1.5h.
[0049] Furthermore, in step S2, the average particle size of the diamond particles is 20 nm, and the average particle size of the prepared nano-diamond silver particles is 80 nm.
[0050] Furthermore, in step S3, the average particle size of the nanosilver particles is 40 nm.
[0051] Furthermore, in step S3, the organic solvent is preferably anhydrous ethanol; the surfactant is preferably polyvinyl pyrrolidone; and the mass ratio of the surfactant to the nanosilver particles is 1:15.
[0052] Furthermore, in step S3, the time for mechanical oscillation using the spiral oscillator is 10 minutes, and the time for ultrasonic stirring using the ultrasonic cleaner is 55 minutes.
[0053] Furthermore, in step S4, the mass ratio of nano-diamond silver particles to nano-silver slurry is 1:25.
[0054] Furthermore, in step S4, the stirring time of the mixer is 1 hour, wherein the mechanical oscillation is firstly performed by a spiral oscillator for 20 minutes, and then the ultrasonic oscillation is performed by an ultrasonic cleaner for 40 minutes.
[0055] The performance of the diamond silver-nanosilver solder thermal conductive material prepared in this example was tested. Due to the excellent thermal conductivity of diamond, the thermal conductivity was measured by a Hot Disk thermal constant analyzer to be 453 W / (m·K).
[0056] Embodiment 2
[0057] The present application provides a method for preparing a diamond silver-nano silver solder paste, which comprises the following steps in chronological order:
[0058] S1: Ultrasonic cleaning and plasma cleaning of diamond particles;
[0059] S2: using magnetron sputtering to deposit a transition layer on the surface of diamond particles, and then coating them with silver to obtain nano-diamond silver particles;
[0060] S3: preparing nano silver slurry: adding 0.7 g of nano silver particles into 35 ml of organic solvent, adding 0.04 g of surfactant, and then mechanically oscillating with a spiral oscillator, and finally ultrasonically stirring with an ultrasonic cleaner to obtain nano silver slurry;
[0061] S4: Preparation of diamond silver-nano silver solder paste: Nano-diamond silver particles are mixed with nano-silver slurry at room temperature, and stirred with a mixer until the particles are evenly dispersed. After washing and centrifugal separation, diamond silver-nano silver solder paste is obtained.
[0062] Furthermore, in step S1, the ultrasonic cleaning step is: under the condition of a vibration frequency of 40kHz, first immerse in acetone for 10 minutes, then immerse in anhydrous ethanol for 5 minutes, rinse the cleaned object with water, then ultrasonically clean it in pure water for 8 minutes, and finally spread it flat in a vacuum environment at 120°C and dry it for 60 minutes.
[0063] Furthermore, in step S1, the plasma cleaning conditions are: plasma cleaning for 20 minutes at a pressure of 5 Pa, an argon gas flow rate of 500 sccm, a temperature of 100° C., and a bias voltage of −800 V;
[0064] Furthermore, the step S2 also includes the following steps:
[0065] S2.1: Select target material: Select a silver target with a purity higher than 99.99% as the sputtering target;
[0066] S2.2: Sputtering transition layer: Cr is selected as the transition layer metal. The applied bias voltage is -80V, the power is 2kW, the gas pressure is 0.5Pa, and the sputtering time is 10min; the thickness of the sputtered Cr layer is 15nm; during the magnetron sputtering process, an ultrasonic vibration system is used to vibrate the diamond particles so that the diamond particles tumble during the deposition process to ensure the uniformity of deposition on each surface of each particle.
[0067] S2.3: Use DC magnetron sputtering to plate a silver coating on the surface of the diamond particles with the transition layer deposited: fill with argon gas, adjust the pressure in the sputtering chamber to 0.5Pa, the sputtering power to 2kW, the bias voltage to -80V, the sputtering time to 20min, and the thickness of the sputtered Ag layer to 25nm. During the magnetron sputtering process, an ultrasonic vibration system is used to vibrate the diamond particles so that the diamond particles roll during the deposition process to ensure the uniformity of deposition on each surface of each particle. Finally, nano-diamond silver particles are obtained.
[0068] S2.4: Heat treatment: Heat treatment is carried out under normal pressure argon atmosphere, the heat treatment temperature is 200°C, and the heat treatment time is 1 hour.
[0069] Furthermore, in step S2, the average particle size of the diamond particles is 40 nm, and the average particle size of the prepared nano-diamond silver particles is 120 nm.
[0070] Furthermore, in step S3, the average particle size of the nanosilver particles is 80 nm.
[0071] Furthermore, in step S3, the organic solvent is preferably anhydrous ethanol; the surfactant is preferably polyvinyl pyrrolidone; and the mass ratio of the surfactant to the nanosilver particles is 1:17.
[0072] Furthermore, in step S3, the time for mechanical oscillation using the spiral oscillator is 20 minutes, and the time for ultrasonic stirring using the ultrasonic cleaner is 45 minutes.
[0073] Furthermore, in step S4, the mass ratio of nano-diamond silver particles to nano-silver slurry is 1:20.
[0074] Furthermore, in step S4, the stirring time of the mixer is 1.5 hours, wherein the mechanical oscillation is firstly performed by a spiral oscillator for 30 minutes, and then the ultrasonic oscillation is performed by an ultrasonic cleaner for 60 minutes.
[0075] The diamond silver-nanosilver solder thermal conductive materials prepared in Example 1 and Example 2 were tested for performance. The test results are shown in Table 1. Due to the excellent thermal conductivity of diamond, the thermal conductivity was measured by a Hot Disk thermal constant analyzer to be 487 W / (m·K).
[0076] Table 1. Performance test results of diamond silver-nanosilver solder thermal conductive materials
[0077]
[0078] Table 1.
[0079] The sintering process of the diamond silver-nano silver solder paste prepared by the method for preparing the diamond silver-nano silver solder paste for welding is as follows Figures 2 to 4 As shown in the figure, due to the large sintering driving force of small-sized nanosilver particles, the surface of the particles melts first, and because the surface of the nanodiamond silver particles is also silver, the small-sized nanosilver particles will aggregate and fuse around the large-sized nanodiamond silver particles after the surface melts; then the intensification of liquid phase diffusion causes the small-sized nanosilver particles and the large-sized nanodiamond silver particles to contact each other to form a sintering neck; finally, under the mechanisms of liquid phase sintering densification and plastic deformation densification, the sintering neck grows, and the pores between the sintering necks shrink and disappear, and the nanosilver particles sinter to form a densified whole.
[0080] During sintering, the nanosilver particles contact each other to form a sintering neck. As the laser power increases, atoms move toward the sintering neck, which causes the sintering neck to grow. The nanosilver particles combine to form a larger whole, achieving densification. In the existing technology for improving the thermal conductivity of nanosilver paste, diamond particles or aluminum nitride particles are usually doped into the nanosilver paste. Since the melting points of diamond and aluminum nitride are very high, it is not easy to form a sintering neck between the nanosilver particles and the diamond particles or aluminum nitride particles during the sintering of the nanosilver paste. Therefore, a large number of pores exist after the final sintering, which greatly reduces the shear strength and conductivity of the sintered joint. In the present application, nanosilver particles with small particle size are doped with nanodiamond silver particles with large particle size. In the present application, nanosilver particles are doped with nanodiamond silver particles. During the sintering process, the nanosilver particles and the nanodiamond silver particles contact and fuse with each other to form a sintering neck, thereby forming a three-dimensional sintering network and continuing to grow three-dimensionally to eventually form a large number of twins. The twin boundaries can effectively hinder the movement of dislocations and improve the strength of the sintered sample. In addition, the twin boundaries have a weak scattering effect on electrons. In addition, the twins that penetrate the grains can introduce low-heavy site lattice grain boundaries with relatively regular atomic arrangement at large-angle grain boundaries, resulting in a sintered structure with very low thermal resistance, overcoming the intrinsic defect of a metal with a nano-grain size that the thermal conductivity is significantly reduced due to the grain boundary scattering effect. On the other hand, the twin boundary resistivity in the nanosilver paste after sintering is only 1 / 40 of the resistivity of ordinary silver grain boundaries, showing excellent electrical conductivity.
[0081] The above embodiments are only for illustrating the technical concept and features of the present application, and their purpose is to enable people familiar with the technology to understand the content of the present application and implement it accordingly, and they cannot be used to limit the protection scope of the present application. Any modifications made according to the spirit of the main technical solution of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing diamond silver-nano silver solder paste, characterized in that: The preparation method comprises the following steps in sequence: S1: Cleaning of nano-scale diamond particles; S2: using a magnetron sputtering process to first deposit a transition layer on the surface of the nano-scale diamond particles, and then deposit a silver coating on the surface of the transition layer to obtain nano-diamond silver particles, wherein the average particle size of the nano-scale diamond particles is 20nm to 40nm, and the average particle size of the prepared nano-diamond silver particles is 80nm to 120nm; S3: adding nanosilver particles into an organic solvent and mixing them evenly to obtain a nanosilver slurry, wherein the average particle size of the nanosilver particles is 40 nm to 80 nm; S4: mixing the nano-diamond silver particles obtained in step S2 with the nano-silver slurry obtained in step S3 at room temperature to obtain diamond silver-nano-silver solder paste; The step S2 also includes the following steps: S2.1: Select target material: Select silver target with purity higher than 99.99% as sputtering target material; S2.2: Sputtering transition layer: The material of the transition layer is selected from one of Ni, Cr, and Ti; the applied bias voltage is -80V to -60V, the power is 0.5kW to 2kW, the gas pressure is 0.2Pa to 1Pa, the sputtering time is 5min to 10min, and the pre-sputtering thickness is 5nm to 10nm; during the magnetron sputtering process, the diamond particles are vibrated based on the ultrasonic vibration system, so that the diamond particles roll during the deposition process; S2.3: using DC magnetron sputtering to plate a silver coating on the surface of the diamond particles on which the transition layer is deposited: filling with argon gas, adjusting the pressure in the sputtering chamber to 0.2Pa-0.5Pa, the sputtering power to 0.5kW-2kW, the bias voltage to -80V--60V, the sputtering time to 10min-20min, and the thickness of the pre-sputtered silver coating to 15nm-25nm; during the magnetron sputtering process, using an ultrasonic vibration system to vibrate the diamond particles so that the diamond particles tumble during the deposition process; S2.4: Heat treatment: Heat treatment is carried out in an atmosphere of argon at normal pressure, the heat treatment temperature is 200°C or 220°C, and the heat treatment time is 1h to 1.5h.
2. The method for preparing diamond silver-nano silver solder paste according to claim 1, wherein The cleaning process in step S1 includes ultrasonic cleaning and plasma cleaning in sequence; The ultrasonic cleaning comprises: soaking the nanometer-scale diamond particles in acetone, soaking them in anhydrous ethanol, ultrasonically cleaning them in pure water, and then drying them in a vacuum environment; The plasma cleaning includes: performing plasma cleaning for 20 minutes to 40 minutes under the conditions of gas pressure of 0.5Pa to 5Pa, argon gas flow rate of 400sccm to 500sccm, temperature of 100°C, and bias voltage of -800V to -500V.
3. The method for preparing diamond silver-nano silver solder paste according to claim 1, wherein: In the step S3: preparing the nano silver slurry further comprises: Add nanosilver particles into an organic solvent containing a surfactant. Then a spiral oscillator is used for mechanical oscillation. Finally, the nanosilver slurry is obtained by ultrasonic stirring.
4. The method for preparing diamond silver-nano silver solder paste according to claim 3, characterized in that: The organic solvent is anhydrous ethanol; The surfactant is polyvinyl pyrrolidone PVP; The mass ratio of the surfactant to the nano-silver particles is 1:13 to 1:
17.
5. The method for preparing diamond silver-nano silver solder paste according to claim 3, characterized in that: The time for mechanical oscillation using the spiral oscillator is 10 minutes to 20 minutes, and the time for ultrasonic stirring using the ultrasonic cleaner is 40 minutes to 60 minutes.
6. The method for preparing diamond silver-nano silver solder paste according to claim 1, characterized in that: In step S4, the mass ratio of nano-diamond silver particles to nano-silver slurry is 1:15 to 1:30; and the mixing and stirring time is 1 h to 1.5 h.
7. A diamond silver-nano silver solder paste, prepared by the preparation method of the diamond silver-nano silver solder paste according to any one of claims 1 to 6.
8. A method for welding using the diamond silver-nano silver solder paste according to claim 7.
Citation Information
Patent Citations
Diamond-nano silver solder paste heat conduction material and preparation method thereof
CN109108524A
Carbon nano-tube / nano-silver soldering paste heat-conduction material and preparing method thereof
CN110549039A
Diamond film based on nanoparticle modification and preparation method thereof
CN112647056A